Local scour at complex bridge piers - Najafzadeh, Mahboubeh (2014)
The prediction of scour depths at bridge piers is a necessary input to the design of the pier foundations. Local scour around bridge foundations is one of the most significant causes of bridge failures. Many studies about local scour around bridge piers have been conducted, but because of difficulties in understanding the nature of flow and scour mechanisms around bridge foundations there remain problems in scour prediction. The main objective of this study is to investigate the local scour at different selected complex piers in the laboratory and to use the collected data for validation of the existing methods for estimation of local scour around complex pier. In addition, the isolated components of complex piers effect on local scour were quantified for each model too. In this study, a methodology for estimating equilibrium local scour depths at complex pier under clear-water conditions at threshold flow intensity is used. This application of the methodology is limited to bridges that are composed of up to three components namely column, pile cap and pile group. All of the components are exposed to the approaching flow. The experimental procedure has been conducted for five selected complex piers from existing bridges in Malaysia to investigate the effect of complex pier shape on local scour. Cohesionless uniform sediment with the mean particle sizes, d50=0.23 mm was used in all the experiments. Flow parameters such as discharge, depth and velocity measured by using an Area Velocity Model (AVM). Apart from the shape of complex piers, the other parameters such as flow intensity, flow depth, sediment size, alignment or angle of attack were kept constant during the experimental procedures. In base of measured data in this study total scour depth of all components of each model is greater than of complex pier. The scour depths measured in the laboratory show among these selected models, model number 3 and 4 have the lower scour depth. In the other words, these two models have the optimum shapes of complex pier compared with the others. The measured values of local scour were compared to compute values obtained from Federal Highway Administration (Hydraulic Engineering Circular No. 18, HEC-18), Florida Department of Transportation (FDOT) and Coleman methods for complex piers. The results show that for predicting local scour at selected complex pier bridges in the same experimental condition, HEC-18 methodology is recommended.